Media Influence and the Willingness to Buy Intangible Cultural Heritage Products: A Moderated Mediator Model. (14th September 2021) - Huang, Yijun; Lv, Qinghua; Lin, Jian
Abstract : In the information society, the media exert a key influence on the consumer selection of intangible cultural heritage (ICH) products. Drawing on the literature of cultural identity, product involvement, and willingness to buy, this paper constructs and verifies the theoretical model of media influence-cultural identity-willingness to buy ICH products, with ICH product consumers as the objects. The results show that the media have a significantly positive effect on cultural identity, which in turn significantly promotes the willingness to buy, but the media do not significantly affect the willingness to buy. Cultural identity fully mediates the media influence on the willingness to buy. Referring to relevant studies on product involvement, the samples were divided into a set of high involvement and a set of low involvement. The moderating effect analysis reveals that the higher the product involvement, the more significant the effect of media on cultural identity and the more prominent the influence of cultural identity on the willingness to buy. Finally, the authors discussed the managerial implications of the research results for ICH inheritors and enterprises.